The regulation of labour and the state in the Sudan : a study of the relationship between the stage of social and economic development and the autonomy of labour relations law - Hussein, El Siddig Abdel Bagi (1986)
The thesis is a study of labour regulation and the State in the Sudan in the light of a general theoretical conception of labour law and the State. The first Chapter defines the concepts of analysis that are used throughout the study, isolates the "essential" properties of the Capitalist State and Law from the historically concrete forms which they assume in a particular society and distinguishes between processes which influence development of the form of law and others which influence its sociological development. Drawing on the analysis in Chapter I, Chapter II exposes the inter-relationship between the Sudanese social formation, State and Law and the implication of this inter-relationship for both the form and substance of labour relations law. Chapters III, IV and V are specific verifications of the hypothesis regarding the inter-relationship between the State and labour relations law in the Sudan and that regarding the development of the "substance" and "ideology" of law in general. The thesis considers law as an empirically-founded discipline. But, it distinguishes between various types of empirical facts about law corresponding with respective semi-autonomous social levels at which law asserts its existence. The research method followed describes the empirical facts about law at the particular level and, in order to determine the epistemological significance of these facts, analytically relates them to empirical facts at other levels. Wherever used in the thesis the term "theory" signifies either this methodological procedure of analysing the inter-connection of empirical facts at a certain level and their inter-relation with other facts at other levels, or the substantive generalizations about law which findings at these various levels would allow. I consider my application of this methodology to the study of labour rela tions law, the historical dimension this application introduces in socio-economic analysis of this law, the criticism of certain Marxist and other sociological conceptions of law it enables, and the socio-histor ical relativity of the "substance" and "ideology" of law it reveals as original contributions to the knowledge of labour law. The compilation and evaluation within the framework of the thesis of empirical materials on industrial relations in the Sudan are likewise original contribution to the knowledge of Sudanese "labour law" and labour law in general.